2016
DOI: 10.1164/rccm.201505-0928oc
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Exposure to Traffic-related Air Pollution and Lung Function in Adolescence

Abstract: Exposure to traffic-related air pollution in infancy is negatively associated with FEV1 at age 16 years, leading to increased risk of clinically important deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 29 publications
7
109
1
2
Order By: Relevance
“…Although some studies have also found proportional associations of air pollution with FEV 1 and FVC in a restrictive pattern (8,13), other studies have found a largermagnitude association with FEV 1 than FVC, suggesting an obstructive effect involving the larger airways (9,30,31). Two recent studies that examined long-term PM 2.5 and BC exposure in the Boston area using the same models as the present study found restrictive patterns of effects on adult lung function and lung function decline (21,32).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Although some studies have also found proportional associations of air pollution with FEV 1 and FVC in a restrictive pattern (8,13), other studies have found a largermagnitude association with FEV 1 than FVC, suggesting an obstructive effect involving the larger airways (9,30,31). Two recent studies that examined long-term PM 2.5 and BC exposure in the Boston area using the same models as the present study found restrictive patterns of effects on adult lung function and lung function decline (21,32).…”
Section: Discussionsupporting
confidence: 43%
“…However, studies by Schultz and colleagues (30,31) of PM 10 exposure in the Stockholm area found that PM 10 exposure in the first year of life was more strongly associated with lung function at age 8 and adolescence than later exposure averages. These studies examined larger particles of PM 10 , which includes PM 2.5 and coarse particles, such as road dust.…”
Section: Discussionmentioning
confidence: 97%
“…30 Previous authors have postulated that the detrimental effects of cigarette smoke may overwhelm the adverse consequences of ambient air pollution exposure. 30 A similar phenomenon may drive the suggestion of a differential effect that we observed in ethnic groups with stronger effects from unmeasured healthcare disparities and other confounders compared to the effects due to air pollution. While our study had enough power to assess for associations with our main outcome of interest, our ability to show effect modification by these variables is limited.…”
Section: Discussionmentioning
confidence: 99%
“…22 At both occasions, spirometry was performed according to American Thoracic Society/European Respiratory Society criteria. 23 The highest values of forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV 1 ) were used for analysis.…”
Section: Measurements Of Lung Functionmentioning
confidence: 99%